2022
DOI: 10.1109/access.2022.3151104
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Surfactants on the Electrical and Rheological Aspects of Silica Based Synthetic Ester Nanofluids

Abstract: This study reports experimental investigations of the effects of different surfactants (CTAB, Oleic acid and Span 80) on silica based synthetic ester nanofluids. The positive and negative potential observed for the ionic (CTAB) and non-ionic surfactant (Span 80) from zeta potential analysis indicates an improved stability. The optimization of nanofillers and surfactants is performed considering the corona inception voltage measured using ultra high frequency (UHF) technique and fluorescent fiber. Rheological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…It is observed that CTAB, as a surfactant, exhibits excellent stability in comparison to the other surfactants, oleic acid and span-80. Similar observations of zeta potential are made with the silica based synthetic ester nanofluids [15]. CTAB being cationic surfactant carries positive charged head attach itself with the hydroxyl group.…”
Section: A Zeta Potential Distribution With Nanofluidssupporting
confidence: 75%
“…It is observed that CTAB, as a surfactant, exhibits excellent stability in comparison to the other surfactants, oleic acid and span-80. Similar observations of zeta potential are made with the silica based synthetic ester nanofluids [15]. CTAB being cationic surfactant carries positive charged head attach itself with the hydroxyl group.…”
Section: A Zeta Potential Distribution With Nanofluidssupporting
confidence: 75%